Thermal comfort assessment of naturally ventilated public hospital wards in the tropics - Noor Muhammad, Abdul Rahman; Chin Haw, Lim; Ahmad, Fazlizan; Azman, Hussin; Muhammad Syukri Imran, Abdullah (Elsevier Ltd., 2021)
Natural ventilation, which is a common method used in tropical climate countries, can provide a high rate of airflow to maintain good indoor air quality and thermal comfort. However, the use of natural ventilation alone as passive cooling strategy is insufficient to improve indoor thermal environment. Thus, this study aims to determine the existing thermal comfort conditions in a naturally ventilated public hospital ward by using three methods: simulation works, objective measurements and field surveys. The combination of all these methods in measuring thermal comfort is essential in acquiring the most accurate results and has yet to be implemented in any public hospital in the tropics on the basis of the literature review conducted. The simulation results presented that more than half of the total occupants in the ward feel discomfort, with a predicted mean vote (PMV) between 1.0 and 1.6 and a predicted percentage of dissatisfied between 40% and 56%. On-site measurements recorded the same PMV reading, indicating slightly warm and warm, on the basis of the ASHRAE Standard 55 assessment scale. By contrast, the results of the survey questionnaire showed a different perception of the occupants, with 82% of the respondents voting in the range of warm to hot scale. The thermal conditions in the naturally ventilated ward studied for two months in 2020 were found to be uncomfortable and required further improvement. Knowledge of the climatic characteristics and the current state of the indoor thermal environment will help the building owners strategise an appropriate bioclimatic design approach